Elterlicher Sozialstatus und andere Determinanten von Lebensqualität und Verhaltensauffälligkeiten: eine Analyse deutscher Frühgeborener der Jahrgänge 1987-2004 = Parental social status and other determinants of quality of life and behavioral problems : an analysis of german preterm births between 1987-2004 - Becker-Grünig, Tabea; Schneider, Sven; Sonntag, Diana; Bock, Freia de (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2016)
Background: Knowledge of the factors affecting the development of preterm children in Germany is limited. We analysed the prevalence of preterm birth in Germany using the German Health Interview and Examination Survey for Children and Adolescents 2003-2006 and assessed factors associated with quality of life (QOL) and behavioural development in preterm children (< 37 weeks’ gestational age). Methods: Data were weighted and preterm prevalence was calculated by socioeconomic status (SES) and year of birth for 1,106 preterm children. Using linear regression models, the relationship between sociodemographic, pre- and perinatal, lifestyle, and contextual determinants on the one hand, and the QOL (KINDL® parent questionnaire) and behavioural problems (the total problem behaviour scale, the Strengths and Difficulties Questionnaire [SDQ]) on the other was calculated. Results: Prevalence of preterm birth (mean 7.5 %) was higher in families with low compared with high SES (8.4 versus 7.0 %). In the final regression models, preterm children with high SES had higher QOL scores (+ 3.3 KINDL points, p = 0.024) compared with children with low SES, and adolescents (aged 14-17 years) had a higher QOL than children aged 7-13 years. All other variables (contextual, pre- and perinatal) were not related to QOL. In contrast, there were many determinants of behavioural development in preterms: the SDQ total score was lower in girls, children with older mothers, those from high SES and those with a high level of physical activity. However, both very low birth weight (< 1,500 g) and birth at > 34 weeks’ gestation were associated with a higher SDQ total score. Conclusion: Given its high prevalence, preterm birth is a relevant public health issue in Germany. While SES may be the most important determinant of QOL in preterms, determinants of behavioural problems are the same as those in term children and also encompass perinatal factors.